Influence of implant positioning in extraction sockets on osseointegration: Histomorphometric analyses in dogs - Caneva, Marco; Salata, Luiz Antonio; Souza, Sergio Scombatti de; Baffone, Gabriele; Lang, Niklaus P.; Botticelli, Daniele (Wiley, 2010)
Aim: To evaluate the influence of implant positioning into extraction sockets on osseointegration. Material and methods: Implants were installed immediately into extraction sockets in the mandibles of six Labrador dogs. In the control sites, the implants were positioned in the center of the alveolus, while in the test sites, the implants were positioned 0.8 mm deeper and more lingually. After 4 months of healing, the resorptive patterns of the alveolar crest were evaluated histomorphometrically. Results: All implants were integrated in mineralized bone, mainly composed of mature lamellar bone. The alveolar crest underwent resorption at the control as well as at the test sites. After 4 months of healing, at the buccal aspects of the control and test sites, the location of the implant rough/smooth limit to the alveolar crest was 2±0.9 mm and 0.6±0.9 mm, respectively (P<0.05). At the lingual aspect, the bony crest was located 0.4 mm apically and 0.2 mm coronally to the implant rough/smooth limit at the control and test sites, respectively (NS). Conclusions: From a clinical point of view, implants installed into extraction sockets should be positioned approximately 1 mm deeper than the level of the buccal alveolar crest and in a lingual position in relation to the center of the alveolus in order to reduce or eliminate the exposure above the alveolar crest of the endosseous (rough) portion of the implant. © 2009 John Wiley & Sons A/S.
Keywords: Animal study; Bone healing; Extraction socket; Implant dentistry; Osseointegration; Placement; Positioning; animal; bone regeneration; denture; dog; histology; jaw; methodology; plastic surgery; tooth extraction; tooth implantation; tooth socket; wound healing; Alveolar Process; Animals; Dental Abutments; Dental Implantation, Endosseous; Dental Implants, Single-Tooth; Dogs; Surgical Flaps; Tooth Extraction; Tooth Socket; Wound Healing